THE EFFECT OF HUMAN RESOURCE DEVELOPMENT ON EMPLOYEE PERFORMANCE AT PT. NUSANTARA PLANTATION V PEKANBARU - Zakaria; Aisyah Rahman; Suyatni (PENANOMICS: International Journal of Economics, 2023)
The purpose of this study was to determine the effect of human resource development on employee performance. This research was conducted with the title "The Influence of Human Resource Development on Employee Performance at PT. Nusantara V Pekanbaru Plantation". The population of this study is only part of the data information that the average number of employees at PT. Perkebunan Nusantara V Pekanbaru about 153 people, the determination of the sample using the census technique method, namely the population was used as the research sample. Therefore, the sample used in this study were 42 respondents, drawn from the human resources, finance and accounting sections and the procurement and IT departments. Data collection techniques in this study used questionnaires and interviews. The data analysis in this study is descriptive analysis and simple linear regression analysis with SPSS version 25 application tools. The results show that partially human resource development variables have a positive and significant effect on employee performance at PT. Perkebunan Nusantara V Pekanbaru, and the results shown in simple linear regression show that the human resource development variable has a positive influence on employee performance at PT. Nusantara V Pekanbaru Plantation.